Diagnostic Utility of Bone Marrow Aspiration Cytology- A Hospital Based Prospective Study at Nepalgunj Medical College - Adhikari, Milan; Ghimire, Pragya Gautam; Shrestha, Richa; Baidya, Pooja; Rayamajhi, Asmita (Journal of Nepalgunj Medical College, 2023)
Introduction: Hematological disorders are common in all age groups and are worldwide in distribution. At times, routine hematological tests are not sufficient to diagnose blood disorders. Bone marrow examination serves as an important diagnostic aid to evaluate various neoplastic and non-neoplastic hematological diseases. Aims: To study role of Bone Marrow Aspiration Cytology in diagnosing hematological disorders. Methods: This is a one-year hospital based prospective study done at Department of Pathology, NGMC, Kohalpur. It included 34 cases subjected to Bone marrow aspiration cytology. Correlation with Peripheral Blood Smear, Reticulocyte count, pearls iron stain and other parameters were done before giving the final diagnosis. Results: Age of patients ranged from 10-82 years with equal gender distribution. Common indications for Bone marrow examination were pancytopenia (50%), followed by Anemia and Thrombocytopenia. Megaloblastic Anemia (n=10,29%) was the commonest Anemia followed by mixed nutritional deficiency and Iron Deficiency Anemia. Hematological Malignancy accounted for six cases, of which Acute Myeloid Leukemia was diagnosed in two cases. Infectious causes comprised of two cases of Visceral Leishmaniasis and one case of Bone Marrow Tuberculosis. Conclusion: Bone marrow aspiration cytology serves as an important adjunct in diagnosing hematological disorders. More reproducible results are obtained if bone marrow biopsy is done in conjucntion with aspiration cytology.